(3GdYhdeI hGdGbJUGOGJ GdhWfjI (B/s - (3GdUGOb, Ydj Jhajbs; (3GdHdHd, CMeO Ydjs ((3CHh XHj(B: s (3UfOhb GdfbO GdYQHj(B, s, 2001)
(3jbOe gPG GdcJGH CYeGd GdfOhI GdJj fXegG UfOhb GdfbO GdYQHj hUfOhb GdfbO GdOhdj Mhd GdYhdeI hEOGQI GdGbJUGOGJ GdhWfjI hYbOJ aj CHh XHj jhej (B18 (3h(B19 (3GdJj MVQgG cHGQ GdeSDhdjf GdYQH, jVe MUjdI GdfOhI(B/ (3ehGLgI JMOjGJ GdYhdeI, GdYhdeI hGdJMOjGJ GdJj JhGLg GdHdOGf GdfGejI, GdYhdeI hJLQHI GdCSjhjI, CeQjcG GddGJjfjI aj YGde jJYhde, GdYhdeI hCSdhH GdEOGQI GdGbJUGOjI, GdSjGSI GdGbJUGOjI GdcdjI ddHfGf aj Xd GdYhdeI(B.s
Keywords: (3GdGbJUGO GdOhdjs; (3GdYhdeIs